Quinolone-induced Torsades De Pointes: A life-threatening complication of conventional medication - Sojikul, Lanlalin; Chongtanapipat, Kunchanit; Chintanavilas, Kumpul (Asian Medical Journal and Alternative Medicine, 2023)
The use of antibiotic drugs, particularly the quinolone group, can cause acquired QT prolongation and blockage of the potassium channel (Ik). We report a case of torsade de pointes (TdP) triggered by the use of ciprofloxacin to treat arteriovenous fistulas infection.